The contributions of age and sex to variation in common tern population growth rate. - Ezard, T; Becker, P; Coulson, T (2006)
1. The decomposition of population growth rate into contributions from different demographic rates has many applications, ranging from evolutionary biology to conservation and management. Demographic rates with low variance may be pivotal for population persistence, but variable rates can have a dramatic influence on population growth rate. 2. In this study, the mean and variance in population growth rate (lambda) is decomposed into contributions from different ages and demographic rates using prospective and retrospective matrix analyses for male and female components of an increasing common tern (Sterna hirundo) population. 3. Three main results emerged: (1) subadult return was highly influential in prospective and retrospective analyses; (2) different age-classes made different contributions to variation in lambda: older age classes consistently produced offspring whereas young adults performed well only in high quality years; and (3) demographic rate covariation explained a significant proportion of variation in both sexes. A large contribution to lambda did not imply a large contribution to its variation. 4. This decomposition strengthens the argument that the relationship between variation in demographic rates and variation in lambda is complex. Understanding this relationship and its consequences for population persistence and evolutionary change demands closer examination of the lives, and deaths, of the individuals within populations within species.